Zero-waste strategy through the empowerment of PKK Ecomitra Wage Sidoarjo in sustainable waste - Yunata, Ersyzario Edo; Ramadhan, Rico; Prihandana, Gunawan Setia; Suaebah, Evi (Jurnal Abmas, 2026)
The increasing volume of household waste in densely populated residential areas is a major challenge for urban environmental management. Limited waste management systems and low household-level waste-sorting practices lead to the accumulation of organic waste, which could cause environmental pollution. Therefore, a sustainable waste management strategy based on community participation is needed. This community service program aims to implement and evaluate a zero-waste strategy by empowering the PKK Ecomitra group in Wage Village, Sidoarjo, through the use of appropriate technologies, including a Dekomposer Dua Sisi (Dedisi) and biopore holes, for processing household organic waste. The program was implemented using a Participatory Action Research (PAR) approach that actively involved partners in planning, socialization, training, technology application, and evaluation. Evaluation was conducted through pretest and posttest methods on 15 indicators of participant knowledge and attitudes. The results showed a significant increase in understanding of the fermentation process, waste sorting skills, awareness of the zero-waste concept, and the use of biopore holes. The overall program achievement rate exceeded 80 percent of the set target. These results indicate that a zero-waste strategy based on collective community decisions and the application of simple technologies is effective in increasing household waste management capacity and behavior, and in supporting the achievement of SDGs 12 and 13.